Analyse d’une expérimentation de service public de covoiturage courte distance au prisme du concept de dispositif - Maylis Poirel (Netcom)
Since the 2000s, many initiatives have attempted to establish short-distance carsharing as an alternative mobility solution to private cars and public transport networks. But if these initiatives trie to replicate Blablacar success on long-distance, it is clear that short-distance carsharing has a slow start. Based on the example of a carsharing public service experiment conducted in the mid-2010s in Île-de-France, the analysis deals with citizens involvment in sustainability-oriented public digital devices. It focuses on how designers, in a collaborative and experimental context, induce users involvment. On the one hand, it explores the physical componants of the "carsharing station" and shows how they are designed to cross the "driver" and "passenger" user flows. On the other hand, it shows that the experimental dimension of the service leads to a process of adjustment to users and non-users feedbacks, giving the effect of a drift progressively moving the service away from its guiding principles. These results shed an original light on the Foucauldian concept of dispositif at the crossroads of interactionist, sociotechnical and communicational approaches.